STUDY ON ENDO-PERIODONTAL INTERRELATIONS IN CASE OF MOLARS WITH CHRONIC FURCATION LESIONS AND PROSTHETICHAL TREATMENT - Liana Aminov; Yllka Decolii; Cristina Antohi; Tudor Hamburda; Antonela Beldiman; Laura Elisabeta Checherita (Romanian Dental Association for Education, 2019)
In practice, there are clinical situations that make diagnosis difficult, particularly in case of endo-periodontal lesions with destructive effect at the furcal level. Sometimes these situations may lead to an incorrect therapeutic approach, the main objective in the treatment of endo-periodontal lesions being the stopping of the inflammatory process and the subsequent loss of the periodontal attachment. The aim of this study was to determine the influence of endodontic diseases on the periodontal tissues of furcal area and the rate of recovery in time after the treatment of radicular perforation which produced chronic injury, using reparative materials. Materials and method: The clinico-radiological study was carried out on a group of 24 molars with chronic furcal lesions. In both cases where the lesion was already present and where it was involuntarily performed, it was attempted to stimulate the restoration of the affected tissue by applying repairing biomaterials, seal the root canals and apply a coronal restoration. Results and Discussions: Based on the results of this study, MTA is required as an excellent material for perforation repair, and calcium hydroxide sealants have great advantages in regenerating periradicular bone tissue and the furcal area. Subsequent to endodontic therapy, in most cases, a prosthetic restoration of the treated tooth was made by applying a post and crown. Conclusions: In the case of the teeth included in this study, the effectiveness of medication based on calcium hydroxide and of the sealants with biostimulating properties was suported by the complete healing of the affected tissues.